Mn(acac)2 and Mn(acac)3 complexes, a theoretical modeling of their L2, 3-edges X-ray absorption spectra. (15th October 2017) - Carlotto, Silvia; Sambi, Mauro; Vittadini, Andrea; Casarin, Maurizio
Graphical abstract: The efficiency of diverse functionals to model the L2, 3 -edges spectral features of Mn(acac)2 and Mn(acac)3 has been tested. Abstract: The DFT/ROCIS method has been used to model the Mn(acac)2 (I ) and Mn(acac)3 (II ) L2, 3 -edges absorption spectra. Non-hybrid (BP86 and PBE), hybrid (B3P, PBE0 and B3LYP) and hybrid meta-GGA (M06) functionals have been considered to test their efficiency in reproducing experimental features. Structural parameters of bothI andII are scarcely affected by the functional selection and the same holds as far as the I L2, 3 -edges absorption spectrum is concerned. At variance to that, the use of the hybrid meta-GGA functional is decisive for a detailed assignment of the II L2, 3 -edges spectral features. The role played by the structural arrangement about the central Mn ion appears less important than the Mn oxidation number in determining the overall spectrum appearance and the spectral features' excitation energies ( EE s). DFT/ROCIS results indicate that, both inI andII, the lower EE side of the L3 intensity distribution mainly includes states having the ground state spin multiplicity ( S = 5/2 inI and S = 2 inII ), whereas states with different spin multiplicity contribute, both inI andII, to the L3 higher EE side. The occurrence of states involving metal to ligand charge transfer transitions and implying low lying empty ligand-based orbitals on the I/II L3 higher EE sides has been further confirmed herein.